UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA SMP SWASTA TRISAKTI 2 MEDAN - Anita . .; Bornok . Sinaga (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2015)
ABSTRACT This study aimed to know how to increase understanding mathematical concepts in the order to determine whether the aplication of cooperative learning model Students Teams Achievment Divisons in class VIII Catholic Secondary School Trisakti II Medan TA 2014/2015. The type of research was a Classroom Action Research. Subjects in this study were 35 students of class VIII-A Catholic Secondary School Trisakti II Medan and the object of this study was an effort to improved students' understanding of mathematical concepts with learning model Students Teams Achievment Divisions. The instruments used in the study was the observation and tests.In granting cycle I obtained that category Students Teams Achievment Divisions  model on function the material. To know the students ability to understand the concept of the given initial test and obtained an average score of 1.96 or students in the low category and only 22,85% to reach understanding the concept of the medium category. After given action on first cycle then given a test of understanding the concept. Of the test results obtained by the average score of students 2.45 or lower category as well as students who have graseped the concept of 19 students (54,28%). Because the percentage of achievment of understanding of the concept has not been reached the administration continue to cycle the action two. After a given action in cycle two of the obtained results of the test by a average score of students 2.95 or in the medium category. From first cycle to second cycle obtained an increase of 10 students a score increased by 0.5. Based on the description above description concluded that increasing students understading of mathematical concepts with cooperative learning model Students Teams Achievment Divisions on the material function in class VIII A Catholic Secondary School Trisakti II Medan TA 2014/2015.  Keywords: Cooperative Learning- Students Teams Achievment Divisions , Learning, Secondary.